Role of chemical mediators and biological factors in tooth movement - Aljarullah, Atheer Hussain; Aloraini, Sultanah Abdullah; Almaghamsi, Shahad Talal; Abanmy, Malak Ahmed; Alzenaidi, Ola Yousef; Alharbi, Hanan Ahmad; Alshammari, Yasmeen Hmoud (International Journal Of Community Medicine And Public Health, 2023)
In recent years, there have been various theories proposed to describe the mechanism causing tooth movement. These theories can be broadly categorized into two perspectives: one focusing on bone as the direct target of mechanical force, and the other highlighting the periodontal ligament (PDL) as the key target. While the direct view suggests that osteoclasts and osteoblasts are directly stimulated by compression and tension stresses, respectively, the indirect view suggests that the PDL responds to orthodontic forces. However, evidence challenges the direct view, as bone does not respond to static forces and implants/ankylosed teeth do not move. The indirect view proposes that orthodontic forces lead to areas of compression and tension within the PDL, causing various cellular responses and inflammatory reactions. Osteoclasts play a crucial role in bone resorption, influencing the rate of tooth movement. Inflammatory mediators, including chemokines, cytokines, prostaglandins, and neuropeptides, are released during orthodontic tooth movement, facilitating osteoclast recruitment and activation. Osteoclast genesis is influenced by factors such as TNF-α, IL-1, IL-6, and prostaglandins. Chemical mediators, including parathyroid hormone, vitamin D3, corticosteroids, and thyroxin, have been explored for their potential to accelerate tooth movement, but their systemic effects and practical application present challenges. Overall, understanding the biology of tooth movement involves considering the interactions among osteocytes, osteoclasts, and osteoblasts, as well as immune cells and inflammatory cytokines. Expediting tooth movement requires further research and the development of effective and safe strategies.